Design and synthesis of amino-substituted N-arylpiperidinyl-based inhibitors of the (immuno)proteasome - Gobec Martina; Obreza Aleš; Jukič Marko; Baumgartner Ana; Mihelčič Nja; Potočnik Špela; Virant Julija; Mlinarič Irena; Stanislav Raščan; Sosič Gobec Izidor (Acta Pharmaceutica)
The constitutive proteasome and the immunoproteasome represent validated targets for pharmacological intervention in the context of various diseases, such as cancer, inflammation, and autoimmune diseases. The development of novel chemical scaffolds of non-peptidic nature, capable of inhibiting different catalytically active subunits of both isoforms, is a viable approach against these diseases. Such compounds are also useful as leads for the development of biochemical probes that enable the studies of the roles of both isoforms in various biological contexts. Here, we present a ligand-based computational design of (immuno)proteasome inhibitors, which resulted in the amino-substituted N-arylpiperidine-based compounds that can inhibit different subunits of the (immuno)proteasome in the low micromolar range. The compounds represent a useful starting point for further structure-activity relationship studies that will, hopefully, lead to non-peptidic compounds that could be used in pharmacological and biochemical studies of both proteasomes.